Interview 11 - Abubakari, Yushawu
This file contains the interview notes with Lukaco. Lukaco (Pseudonymize) is 19 years old and has been in the scamming industry for 3 years. Lukaco combines the scamming with his education at the senior high school. While a student Lukaco takes the financial responsibility of his father, mother, 2 elder brothers, and 2 younger siblings. Lukaco is next to the leader in their group. Lukaco has people working under him as well. Lukaco’s boss has international cooperation with hackers in Nigeria and Egypt. The interview was done at the researcher’s place of residence.